Circulation and stratification drivers during the summer season in the upwelling bay of Paracas (Peru): A modelling study. (1st February 2023) - Arellano, Cinthia; Echevin, Vincent; Merma-Mora, Lander; Chamorro, Adolfo; Gutiérrez, Dimitri; Aguirre-Velarde, Arturo; Tam, Jorge; Colas, Francois
Abstract: The circulation and stratification in the shallow semi-enclosed bay of Paracas located downstream of the main upwelling cell off the Peruvian coast were studied during the summer season using a regional circulation model and in situ observations. A downscaling strategy based on a series of three embedded grids, from 10 km to 500 m resolution in the bay allows to take into account the influence of remote perturbations on the bay dynamics. Debiased surface winds from a high-resolution regional atmospheric model were used to force the model. The shortwave absorption depth was parameterized using satellite measurements of surface chlorophyll. Sensitivity experiments to the model forcing and parameterizations were performed to investigate the impact of the wind diurnal variability, tidal forcing, freshwater discharge from a nearby river and shortwave absorption depth on the bay stratification. Results show that: debiasing the wind intensity reduced the model cold bias in the bay and increase the stratification; a shallow shortwave absorption depth induced a cooling of the subsurface water, increasing the stratification; freshwater discharge from the Pisco river north of the bay increased slightly the stratification in the bay during days of weak wind. The high sensitivity of the bay stratification to the atmospheric forcing calls for the need to use more realistic wind forcing products. The circulation in the bay under strong (>5.5 m s −1 ) and weak (<3 m s −1 ) winds was also examined. The summer circulation during strong upwelling-favorable wind conditions was characterized by northward surface currents transporting the bay surface waters outward and subsurface currents transporting cold deeper waters into the bay along its western shore. During weak wind conditions, the current is outward in the bottom layer and a surface southward current related to the poleward undercurrent flowing over the continental slope and shelf transported warm waters into the bay, generating a cyclonic circulation in the bay. Highlights: Summer circulation and stratification in Paracas bay are modeled. Wind forcing impacts strongly on the bay stratification. Chlorophyll-dependent shortwave absorption depth increases stratification. Tidal forcing in the bay is weak. Circulation patterns in the bay depends on the wind strength.